Gender-related indicators and income per capita across Indonesian provinces - Melliny, Vinny Dwi; Pertiwi, Rasyida; Aini, Halia Butra (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
Gender inequality remains a persistent challenge in Indonesia, characterized by substantial disparities in women's labor-force participation, educational attainment, and economic outcomes. This study investigates the relationship between gender-related indicators and provincial income per capita across 34 Indonesian provinces during 2017–2021. Using balanced panel data and panel regression analysis, the Common Effects Model (CEM) was selected as the preferred estimation approach based on the Chow, Hausman, and Breusch–Pagan Lagrange Multiplier tests. The results indicate that male life expectancy, male average years of schooling, male expenditure, female labor-force participation, and economic growth are positively and significantly associated with provincial income per capita. In contrast, female average years of schooling and female expenditure exhibit negative, statistically significant coefficients, suggesting that improvements in female human capital and household welfare have not yet translated into higher regional income, possibly because of labor-market segmentation, occupational mismatch, and unequal access to productive employment. The findings also show that the inclusion of female-related variables substantially improves the model's explanatory power, while economic growth does not materially alter the estimated relationships. These results highlight the importance of complementing investments in women's education with policies that facilitate their integration into productive labor markets. Strengthening the alignment between education and labor-market demand, expanding employment opportunities for women, and enhancing the implementation of gender-responsive budgeting are essential to promoting more inclusive and sustainable regional economic development in Indonesia.